GOVERNANCE STRATEGIES TO ALLEVIATE POVERTY IN TASIKMALAYA CITY - Yuliawati, Fitriyani; Larasati, Endang; Lituhayu, Dyah (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
Poverty reduction remains a major challenge in Indonesia. Although government reports always show a yearly decrease in poverty, this is not always accurate. The same situation occurred in Tasikmalaya City. In 2020, Tasikmalaya City was identified as the poorest city in West Java. Despite a decline in the poverty rate in Tasikmalaya City, from 12.72% in 2022 to 11.53% in 2023, poverty remains a significant issue. This research aims to examine how the government manages and controls poverty in Tasikmalaya City. The study uses a qualitative approach. Key informants were selected through purposive sampling. Primary data was collected via interviews and observations, while secondary data came from literature and document studies. Data analysis employed triangulation based on Miles and Huberman. The findings indicate that government governance has not effectively impacted poverty reduction; collaboration, particularly regarding poverty alleviation programs, has not been carried out optimally. Recommendations suggest that the government should apply the principles of good governance to improve collaboration among OPDs in implementing poverty reduction programs.gb777